2019
DOI: 10.1002/pbc.28028
|View full text |Cite
|
Sign up to set email alerts
|

Targeted fusion analysis can aid in the classification and treatment of pediatric glioma, ependymoma, and glioneuronal tumors

Abstract: Background The use of next‐generation sequencing for fusion identification is being increasingly applied and aids our understanding of tumor biology. Some fusions are responsive to approved targeted agents, while others have future potential for therapeutic targeting. Although some pediatric central nervous system tumors may be cured with surgery alone, many require adjuvant therapy associated with acute and long‐term toxicities. Identification of targetable fusions can shift the treatment paradigm toward earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…It was first reported in a 3-month-old female with HGG who did well with gross total resection alone but 4 years later had a recurrence/new tumor of a LGG (ganglioglioma) with the identical fusion [ 11 , 12 ]. This fusion was also observed in an 8-year-old female with a myxopapillary ependymoma in the cauda equina who underwent gross total resection and had been disease free for over 8 years [13] . A recent study detected PPP1CB-ALK fusion in a 10month-old infant with a low-grade glioma and in a newborn with a congenital HGG [3] .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It was first reported in a 3-month-old female with HGG who did well with gross total resection alone but 4 years later had a recurrence/new tumor of a LGG (ganglioglioma) with the identical fusion [ 11 , 12 ]. This fusion was also observed in an 8-year-old female with a myxopapillary ependymoma in the cauda equina who underwent gross total resection and had been disease free for over 8 years [13] . A recent study detected PPP1CB-ALK fusion in a 10month-old infant with a low-grade glioma and in a newborn with a congenital HGG [3] .…”
Section: Discussionsupporting
confidence: 53%
“…Recent in vitro and in vivo studies have demonstrated that the PPP1CB-ALK fusions were tumorigenic, and tumor cells and xenograph tumors harboring PPP1CB-ALK fusion exhibited sensitivity to ALK-inhibitors [ 3 , 24 ] . The majority of the few PPP1CB-ALK fusion positive brain tumors are reported to have relatively good outcomes by gross total resection [11][12][13] . Unfortunately, our patient passed away on day two of the life because the size of the tumor, the age of the patient and the neurological comprise at birth made the risk of surgery prohibitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a CIC – NUTM1 gene fusion or a CIC frameshift deletion, not a CIC – LEUTX gene fusion and a CIC amplification, were detected in CNS EFT– CIC . In review of the literature, we found only three cases of the CIC – LEUTX gene fusion were reported in CNS, namely a case of CNS angiosarcoma, a case of anaplastic ganglioglioma, and a case of anaplastic astrocytoma with epithelioid GBM features ( 7 , 8 ) ( Table 1 ), and this is the first case of CIC – LEUTX gene fusion in a CNS embryonal tumor.…”
Section: Discussionmentioning
confidence: 97%
“…Pediatric diffuse low and high-grade gliomas are undergoing significant changes in terms of diagnostic assessment, due to the increasing importance of molecular markers for classification and stratification [10,112,113]. These tumors also harbor peculiar molecular profiles which vary significantly from adult tumors, even in cases with similar histological features.…”
Section: Ntrk Fusions In Pediatric Cns Tumorsmentioning
confidence: 99%